(untitled) (International journal of medical sciences, 2026)
Background: Viral hepatitis remains a significant public health challenge. Despite the availability of highly effective direct-acting antivirals, a substantial proportion of patients delay evidence-based treatment in favor of unverified traditional medicine. The patient's level of health literacy is hypothesized to be a critical determinant in this decision-making process. Objective: To investigate the correlation between the level of health literacy and the frequency of utilizing traditional medicine methods among patients diagnosed with chronic viral hepatitis. Methods: A cross-sectional study was conducted involving 84 patients with chronic viral hepatitis (B and C). Health literacy was quantitatively assessed using the validated HLS-EU-Q16 questionnaire, categorizing patients into adequate, problematic, and inadequate health literacy groups. The use of traditional medicine (herbal remedies, cupping therapy, animal-derived products) and the delay in seeking professional medical care were evaluated through a structured survey. Results: Out of 84 patients, 32.1% (n=27) demonstrated inadequate health literacy. A strong inverse correlation was identified between health literacy scores and the reliance on traditional medicine (r = -0.68, p < 0.01). In the inadequate health literacy group, 81.4% of patients frequently used traditional remedies prior to or instead of seeking antiviral therapy, compared to only 18.1% in the adequate health literacy group (p < 0.01). Furthermore, low health literacy was significantly associated with a delayed initiation of specific antiviral treatment (average delay of 14.5 ± 3.2 months). Conclusion: There is a profound inverse relationship between health literacy and the use of traditional medicine in viral hepatitis management. Inadequate health literacy drives patients toward unproven alternative therapies, risking potential hepatotoxicity and disease progression. Enhancing patient education is paramount for improving adherence to standard antiviral protocols.